2014
DOI: 10.3325/cmj.2014.55.562
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac allograft vasculopathy: diagnosis, therapy, and prognosis

Abstract: Development of cardiac allograft vasculopathy represents the major determinant of long-term survival in patients after heart transplantation. Due to graft denervation, these patients seldom present with classic symptoms of angina pectoris, and the first clinical presentations are progressive heart failure or sudden cardiac death. Although coronary angiography remains the routine technique for coronary artery disease detection, it is not sensitive enough for screening purposes. This is especially the case in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 122 publications
(123 reference statements)
0
37
0
10
Order By: Relevance
“…Cardiac allograft vasculopathy is a difficult disease to diagnose, and regular surveillance is fundamental for early detection. The earlier it is detected, the better the outcomes for these patients . Invasive modalities such as CA and IVUS are most commonly used to detect CAV .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac allograft vasculopathy is a difficult disease to diagnose, and regular surveillance is fundamental for early detection. The earlier it is detected, the better the outcomes for these patients . Invasive modalities such as CA and IVUS are most commonly used to detect CAV .…”
Section: Discussionmentioning
confidence: 99%
“…The earlier it is detected, the better the outcomes for these patients. 36 Invasive modalities such as CA and IVUS are most commonly used to detect CAV. 5,6 However, the risks associated with cardiac catheterization including high cost, risk of radiation, and contrast exposure mandate the need for a noninvasive imaging alternative.…”
Section: Discussionmentioning
confidence: 99%
“…U pacjentów po przeszczepieniu z powodu odnerwienia serca nie obserwuje się typowych dolegliwości stenokardialnych, a ich pojawienie się sugeruje zaawansowanie procesu chorobowego [12]. Pierwszymi objawami częściej występującymi niż w przypadku klasycznej miażdżycy tęt-nic wieńcowych są objawy niewydolności serca, zaburzenia rytmu lub nagły zgon sercowy [13].…”
Section: Diagnostykaunclassified
“…Pozwala na zaobserwowanie dwufazowości CAV, polegającej na początkowym pogrubieniu błony wewnętrznej, z zachowaniem światła naczynia oraz zmianach o charakterze zwężenia, do których dochodzi w późniejszym rozwoju choroby [16]. Wykonanie IVUS 4-6 tygodni oraz rok po Htx pozwala wykryć chorobę wieńcową przekazaną od dawcy, wczesne zmiany w naczyniach, a także może dostarczyć informacji prognostycznych [12]. W badaniu wieloośrodkowym z zastosowaniem IVUS wykazano, że [18].…”
Section: Diagnostykaunclassified
“…Shortterm survival has improved significantly with better immunosuppressive therapy and improved surgical techniques. However, recent findings have also revealed that the major determinants of patient long-term survival are malignancy and cardiac allograft vasculopathy (CAV), which is also known as transplant coronary artery disease or cardiac transplant vasculopathy (6,7). Multiple experimental and clinical studies have shown that vascular smooth muscle cell (VSMC), especially its migration, proliferation and apoptosis (8)(9)(10), plays an important role in the formation of CAV.…”
Section: Introductionmentioning
confidence: 99%